Twin elephants born in Addo - Woodd, Anna (Pachyderm, 1998)
Founded in 1931 with 11 elephants, Addo's present population now stands, with no immigration, at over 285. (n - 286, February 1999) A record number of births in 1998 totalled 29 calves including the first recorded set of twins, two females. Both survived for almost two months, but the young 18 year old who had had only one calf prior to this was apparently unable to provide sufficient milk for two. The smaller of the two died.